A Study on Temporal Variation of Snow and Glacier in Langtang Basin - Devkota, Nirajan; Shakya, Narendra Man (Kathford Journal of Engineering and Management, 2023)
Snow cover and glacier in the Himalaya play a major role for generating stream flow in South Asia. It is already observed that the snowline is retreating in the Himalaya region. While there are relatively more studies on glaciers fluctuation in this region, studies on snow cover are relatively rare. Present study is aimed to analyze the temporal variation of snow and glacier cover (both debris and clean ice covered) of Langtang area within the catchment 432.32 sq.km at outlet 28°12'10.78"N and 85°27'44.58"E. Currently, we used intermittent medium resolution satellite imageries (Landsat) to study the fluctuation in snow cover and glacier area in the Langtang catchment. Our analysis revealed that the glaciers in the study area are tentatively shrinking in average. More specifically, the Landsat Satellite images of the concerned area processed through ERDAS Imagine and their detailed analysis conducted in ArcGIS show that the minimum snow coverage area is declining and maximum snow coverage is in the average range and in the case of debris coverage glacier and clean ice glacier, the trend is declining. The novelty of this study was to develop a robust process having potentiality to predict snow coverage that would be ultimately applicable to agricultural sectors.